Arbitrase Islam di Indonesia - Zein, H Satria Effendi M.; Badan Arbitrase Muamalat Indonesia; Bank Muamalat Indonesia (Jakarta : Badan Arbitrase Muamalat Indonesia, 1994)
Arbitration and award in Indonesia according to Islamic law; collection of papers.
Includes index.
Keywords: Arbitration and award (Islamic law); Arbitration and award -- Indonesia